Pendampingan Peningkatan Kemampuan Bahasa Inggris Santri di Pondok Pesantren - Yuyun Bahtiar; Ahmad Kanzul Fikri; Nur Khasibah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
In addition to studying in formal schools, Students (Santri) can also study in non-formal schools such as participating in training to increase their understanding of a lesson. However, to be able to participate in the training certainly costs a lot. The symptoms found were that some of the students came from underprivileged families, found it difficult to divide study time with their busy lives at the Islamic Boarding School Darul Ulum Widang - Tuban, lacked interest in learning English, and did not have English manuals or other than textbooks from school. This service activity aims to improve the students' English through training at the Islamic Boarding School Darul Ulum Widang - Tuban. The method used in this service activity is fun training in the form of games, singing, and short conversations. The result of this service is that the students' English skills have increased with this training as evidenced by the increase in the average score of the students' English from 31.66 on the initial test to 65.83 on the final test, it can be concluded that using the training method is an effective way to improve Students' English at Islamic Boarding School Darul Ulum Widang - Tuban.